Transonic airfoil design and optimisation by using vibrational genetic algorithm - Hacıogˇlu, Abdurrahman; Özkol, I˙brahim (Emerald, 2003)
In this study, the power of vibrational genetic algorithm (VGA) for transonic airfoil design and optimisation problems, which are generally characterized by multi‐model topology in the design parameter space, has been introduced. This type of problem is characterized by search and computational time to achieve satisfying solutions. In order to obtain more robust and faster algorithm, vibration concept, our earlier study, is further developed. This developed VGA is coupled with a full potential flow‐field solver for inverse design and airfoil optimisation problem in transonic case. The performance of this implemented strategy is compared with that offered by a classical or more commonly used genetic algorithm.